Earnings management in Malaysian public listed family firms - Teh, Boon Heng; Ong, Tze San; Lau, Yi Ying (UKM Press, Universiti Kebangsaan Malaysia, 2017)
The rise of accounting-related scandals has highlighted the prevalence of earnings management in financial markets. This paper offers empirical evidence on the motivations for earnings management in Malaysia public listed family firms. A sample of 100 family firms were randomly selected from Bursa Malaysia from the years 2010 to 2014, which resulted in 500 observations in total. The results indicate that the equity ownership held by a controlling family is associated with the earnings management in the firm, since the controlling family has greater power and rights in decision-making. However, the involvement of the controlling family as board of directors is not associated with earnings management in the family firm, since the non-executive member of the board will become the chairman to oversee and monitor the business operations of the family firm. The indirect ownership of the controlling family in family firms does not provide greater opportunity for them to manage earnings through direct equity shares held by other family members because they have limited power through indirect ownership.